DELPHI METHOD: THE DEVELOPMENT OF ROBOTIC LEARNING SURVEY IN TERTIARY EDUCATION - Mat Nashir, Irdayanti; Yusoff, Abdullah; Khairudin, Moh; Idris, Muhammad Ridzuan; Imam Ma'arof, Nurul Nazirah (Universitas Ahmad Dahlan, 2019)
This article clarify the development of instrument which is related with robotic based learning by using the Delphi methods. The Delphi method provides the chance for researchers to gather input from participants without demanding them to work face-to-face. Often, the process is used to find consensus among experts who have different opinions and observations. The Delphi method enables group problem-solving using an iterative process of problem definition, discussion, feedback, and revisions. This paper discussed the basics of the Delphi method, its application potential, the selection of expert panels and the means on how consensus can be reached among the participants and also the procedure to obtain the final criteria of robotic learning which is 67 from 188 initially.